POTENTIAL AND BENEFITS OF SIJENTIKFRUIT (Baccaurea polyneura) AS A FUNCTIONAL FOOD FOR HEALTH - Ranggi, Ranggi (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
The sijentik fruit (Baccaurea polyneura) is a tropical fruit with potential as a functional food due to its rich bioactive content, including β-carotene, vitamin C, flavonoids, polyphenols, and tannins. These compounds exhibit antioxidant, anti-inflammatory, antimicrobial, and anticancer properties, providing significant health benefits. Despite its great potential, research on its health benefits and applications in the food industry remains limited. Therefore, this study aims to review the nutritional composition, bioactive compounds, and potential utilization of si jentik fruit in the food sector, based on a scientific literature review.This study employed a literature review method by identifying, evaluating, and synthesizing various studies related to the nutritional content, bioactive compounds, and health benefits of si jentik fruit. Data were obtained from scientific articles, books, and publications in electronic databases such as Google Scholar, PubMed, and ScienceDirect. The inclusion criteria consisted of articles published within the last ten years, relevant to functional food and health aspects. The review findings indicate that si jentik fruit has high antioxidant activity, contributing to a reduced risk of degenerative diseases such as cardiovascular disease, diabetes, and cancer. The flavonoids in this fruit exhibit anti-inflammatory properties, which help reduce chronic inflammation. In the food sector, si jentik fruit can be utilized as a functional beverage ingredient, natural colorant, natural preservative, and as an additive in processed food products such as jams, syrups, and bread. Fermentation has also been shown to enhance the antioxidant activity of si jentik fruit, allowing for its application in probiotic products and nanoencapsulation technology.